Gestão de recursos públicos no âmbito da gestão escolar na perspectiva democrática: uma análise do Programa Dinheiro Direto na Escola (PDDE)em uma escola na rede municipal de Paço do Lumiar/MA - Souza, Kelly Maria Elieuza Alves Lima de (2023)
This Dissertation aimed to analyze, in the light of the principles of democratic management, the management of resources from the Dinheiro Direto na Escola Program (PDDE) in a school of the municipal public teaching network of Paço de Lumiar/MA in the period from 2016 to 2021, seeking to understand how the school community participates, through representatives of the School Board in the management of resources. They gave theoretical-conceptual support to the understanding and analysis of the phenomenon, Araújo (2010; 2013; 2018); Abrucio (2005, 2010); Golden (2007, 2010, 2014, 2016); Paro (2002, 2007, 2009, 2016); Fleury (2003); Lück (2009), in addition to others. The research adopted a dialectical look (KOSIK, 2007) and a qualitative approach, using observation, document analysis and semi-structured interviews as procedures, using content analysis for data analysis and systematization, based on Bardin (2016) and Franco (2008). The school manager, pedagogical coordinator, teachers, and members of the School Council, representative of the Secretary of Education of the Municipality SEMED, participated in the research. The study found the importance of democratic management of education and the public school, as bases that support participatory democracy, as well as the role of collegiate bodies representing the school community in the organization of the school management system, particularly in the management of financial resources of the PDDE. The evidence pointed out in the investigation leads to the conclusion that the principles of school management from a democratic perspective are still poorly understood by the community, particularly the instances represented in the School Council, which points to enormous challenges in the sense of guaranteeing the effective participation of the community, both in the organization of the school management system, as well as in the management of the PDDE Resources in the school. This confirms the need and importance of continuing education at school, with a view to fostering theoretical-practical and critical content for effective community participation, both in administrative and pedagogical management, and in the management of PDDE resources. As a contribution, a Technological Technical Product (PTT) was prepared, containing a proposal for a Training Plan for School Counselors to subsidize continuing education at school. It is a pedagogical notebook with theoretical/practical guidelines, drawn from the results of research in the field school, as well as the legal foundations of education and literature on the subject